Pengembangan Media Pembelajaran Interaktif Berbasis Canva untuk Meningkatkan Motivasi Belajar pada Mata PelajaranPendidikan Agama Islam - Muhammad Muhammad; Yunita Asman; Dira Abdi; Desy Sary Ayunda; Novi Sari Liani (Educational Journal, 2026)
The use of digital learning media is one strategy to enhance the quality of Islamic Religious Education instruction, particularly by creating a more engaging learning atmosphere and boosting student motivation. However, the learning process is often dominated by lecture-based methods, leading to passive student engagement and boredom. One viable alternative is the use of Canva-based learning media, which can present material in a visual, systematic, and interactive manner. This study aimed to develop Canva-based learning media focused on the topic of *tayammum* (dry ablution) to increase student learning motivation at SMP IT Daarul Muttaqien Trienggadeng. The study employed the Research and Development (R&D) method using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, and documentation. The results indicate that the developed learning media functioned effectively within the instructional process. The use of Canva-based digital posters enabled the teacher to deliver material in a more engaging and organized way; consequently, students appeared more focused and actively participated in the lesson, demonstrating higher learning motivation compared to instruction relying solely on lectures. Thus, Canva-based learning media is a suitable alternative for Islamic Religious Education, supporting a learning process that is more effective, interactive, and student-centered.